State-of-the-art review of the clinical research on menopause and hormone replacement therapy association with Parkinson’s disease: What meta-analysis studies cannot tell us - Unda, Santiago R.; Marciano, Sabina; Milner, Teresa A.; Marongiu, Roberta (Frontiers in Aging Neuroscience, 2022)
The menopause is a midlife endocrinological process that greatly affects women’s central nervous system functions. Over the last 2 decades numerous clinical studies have addressed the influence of ovarian hormone decline on neurological disorders like Parkinson’s disease and Alzheimer’s disease. However, the findings in support of a role for age at menopause, type of menopause and hormone replacement therapy on Parkinson’s disease onset and its core features show inconsistencies due to the heterogeneity in the study design. Here, we provide a unified overview of the clinical literature on the influence of menopause and ovarian hormones on Parkinson’s disease. We highlight the possible sources of conflicting evidence and gather considerations for future observational clinical studies that aim to explore the neurological impact of menopause-related features in Parkinson’s disease.